2022
DOI: 10.1111/dme.14793
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of do‐it‐yourself artificial pancreas system compared with continuous subcutaneous insulin infusions in combination with free style libre in people with type 1 diabetes

Abstract: Aims:The use of do-it-yourself artificial pancreas systems (DIYAPS) among people with type 1 diabetes is increasing. At present, it is unclear how DIYAPS compares with other technologies such as FreeStyle Libre (FSL) and continuous subcutaneous insulin infusion (CSII).The aim of this analysis is to compare safety, effectiveness and quality-of-life outcomes of DIYAPS use with the addition of FSL to CSII.Method: Data from two large UK hospitals were extracted from the Association of British Clinical Diabetologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Evidence of similar benefits has also been derived from qualitative studies, including content analysis of data shared through Twitter (subsequently rebranded X), which also demonstrated reduced diabetes burden [16,17]. A total of 2 small studies (N=35 and N=15) using validated PROMs have demonstrated benefits for diabetes distress [14] and fear of hypoglycemia [18]. Recently, a larger cohort study (N=239) found significant improvements, from baseline to 6 months of open-source AID use, in diabetes distress, sleep quality, fear of hypoglycemia, and hypoglycemia confidence [19].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Evidence of similar benefits has also been derived from qualitative studies, including content analysis of data shared through Twitter (subsequently rebranded X), which also demonstrated reduced diabetes burden [16,17]. A total of 2 small studies (N=35 and N=15) using validated PROMs have demonstrated benefits for diabetes distress [14] and fear of hypoglycemia [18]. Recently, a larger cohort study (N=239) found significant improvements, from baseline to 6 months of open-source AID use, in diabetes distress, sleep quality, fear of hypoglycemia, and hypoglycemia confidence [19].…”
Section: Introductionmentioning
confidence: 82%
“…In contrast to commercial systems, there has been relatively little research into the psychosocial outcomes of those using open-source AID systems. Early surveys showed benefits for sleep and QoL but were limited by the use of study-specific (unvalidated) survey questions [12,14,15]. Evidence of similar benefits has also been derived from qualitative studies, including content analysis of data shared through Twitter (subsequently rebranded X), which also demonstrated reduced diabetes burden [16,17].…”
Section: Introductionmentioning
confidence: 93%
“…10,11 In addition to these findings, others have compared DIY APS to commercial systems, often with favourable glucose outcomes (despite often lower HbA1c and higher time-in-range at baseline) and reassuring safety data. [12][13][14] It is difficult to draw conclusions from observational data but with the systems being actively used in the real world there were limited other means to understand them better in the current cohort of users. That being said, AndroidAPS has recently been put through a randomised controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that open-source AID systems have the potential to improve clinical outcomes in users of several age groups (e.g. better HbA1c-level and time in range (TIR)) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Moreover, they reduce the individual burden of living with diabetes, such as improving quality of life and sleep quality (14,(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%